2003
DOI: 10.1046/j.1365-2419.2003.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Forage and migration habitat of loggerhead (Caretta caretta) and olive ridley (Lepidochelys olivacea) sea turtles in the central North Pacific Ocean

Abstract: Satellite telemetry from 26 loggerhead (Caretta caretta) and 10 olive ridley (Lepidochelys olivacea) sea turtles captured and released from pelagic longline fishing gear provided information on the turtles’ position and movement in the central North Pacific. These data together with environmental data from satellite remote sensing are used to describe the oceanic habitat used by these turtles. The results indicate that loggerheads travel westward, move seasonally north and south primarily through the region 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
315
2
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(347 citation statements)
references
References 9 publications
(28 reference statements)
22
315
2
8
Order By: Relevance
“…Therefore, schooling behaviour of prey organisms plays a major role in the feeding success of marine fish predators that roam the open sea, often in shoals (Ménard & Marchal 2003 and eddy-eddy interactions likely enhance biological production in otherwise poor waters, sustaining stocks of potential prey for micronektonic species through bottom-up processes. The micronekton, in turn, can be sought out by upper trophic level predators such as tuna and tuna-like species (Seki et al 2002, Domokos et al 2007), turtles (Polovina et al 2004, Lambardi et al 2008 or seabirds (Nel et al 2001, Weimerskirch et al 2004, Hyrenbach et al 2006. Indeed, several tropical seabird species rely to a large extent on the association with subsurface predators such as tuna, which concentrate prey organisms at the surface while hunting, thus allowing birds to snatch their prey at or above the sea surface (Le Corre & Jaquemet 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, schooling behaviour of prey organisms plays a major role in the feeding success of marine fish predators that roam the open sea, often in shoals (Ménard & Marchal 2003 and eddy-eddy interactions likely enhance biological production in otherwise poor waters, sustaining stocks of potential prey for micronektonic species through bottom-up processes. The micronekton, in turn, can be sought out by upper trophic level predators such as tuna and tuna-like species (Seki et al 2002, Domokos et al 2007), turtles (Polovina et al 2004, Lambardi et al 2008 or seabirds (Nel et al 2001, Weimerskirch et al 2004, Hyrenbach et al 2006. Indeed, several tropical seabird species rely to a large extent on the association with subsurface predators such as tuna, which concentrate prey organisms at the surface while hunting, thus allowing birds to snatch their prey at or above the sea surface (Le Corre & Jaquemet 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that eddies markedly enhanced geochemical transformations and primary production in the subtropical Pacific Ocean (Seki et al 2001, BenitezNelson et al 2007, in the Atlantic Ocean (McGillicuddy et al 1998, Garçon et al 2001, in the Bering Sea (Mizobata et al 2002) and in the Indian Ocean (Quartly & Srokosz 2004, Waite et al 2007). Mesoscale eddies also affect the upper-trophic-level organisms by influencing the horizontal and vertical distribution of mesozooplankton and fish larvae (Bakun 2006, Muhling et al 2007, affecting movement patterns of turtles (Polovina et al 2004, Lambardi et al 2008, attracting tuna (Young et al 2001) or swordfish (Seki et al 2002), and influencing the foraging strategy of seabirds (Nel et al 2001, Weimerskirch et al 2004, Hyrenbach et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, this species, which often exhibits mass nesting in the hundreds of thousands of individuals, is highly numerous, and at particularly high densities in some areas, leading to entanglement hotspots (Jensen et al 2006, Koch et al 2006, Wallace et al 2010a). Secondly, the olive ridley forages along major oceanic fronts which are known to aggregate marine debris (Polovina et al 2004, McMahon et al 2007). Finally, their generalist feeding behaviour potentially attracts them to feed opportunistically on biofouled marine debris such as ghost gear (Stelfox et al 2016).…”
Section: Species Differencesmentioning
confidence: 99%
“…Understanding water column use can influence fisheries management strategies such as gear set depth, soak time, and gear type . For example, in the North Pacific, Polovina et al (2003) used turtle dive data to determine that banning shallower set longlines would decrease the amount of bycatch for sea turtles, specifically loggerheads (Caretta caretta) and olive ridley turtles, because they spent most of their time in the upper water column. Presently, little is known about dive behavior of olive ridley turtles and even less is known about their dive behavior during the internesting period.…”
Section: Introductionmentioning
confidence: 99%